Flora of Paraíba, Brazil: Portulacaceae Juss. and Talinaceae Doweld - Albuquerque, Igor Meneses Cavalcanti de (2022)
The present work comprises the taxonomic survey of Portulacaceae Juss. and Talinaceae Doweld for the State of Paraíba, Brazil. From August/2016 to April/2018, collections and field observations were carried out, complemented by analyzes of the collections of local herbaria (EAN, HACAM and JPB). The identifications of genera and species were carried out with the help of specialized literature for Portulacaceae and Talinaceae. Nine species were recorded in two genera: Portulaca L. (Portulacaceae), with seven species, among which Portulaca grandiflora Höok., as a new record for the flora of Paraíba State and Talinum Adans. (Talinaceae), with two species present in the studied area. Morphological descriptions, keys to families, genera and respective species were made, as well as data on geographic distribution, habitats, flowering and/or fruiting, images, ink prints and comments on taxonomic affinities based on vegetative and reproductive characteristics for the species.